2013
DOI: 10.1111/joss.12046
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Thresholds of Limonin and Nomilin in Bitterness Perception in Orange Juice and Other Matrices

Abstract: Limonin and nomilin are two bitter compounds present in citrus and are thought to cause off‐flavor in Huanglongbing (HLB)‐infected fruit/juice. This study determined the best estimate thresholds of limonin, nomilin and their combination in matrices composed of sugars and acids at levels found in orange juice, and in orange juice, using the three‐alternate forced‐choice methodology. Further, the effect of sucrose or citric acid in orange juice on the bitterness perception of both compounds was investigated. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Kimball [41] pointed out that dilution and degradation during ripening causes a reduction in limonin levels. Dea et al [42] reported that limonin and nomilin were shown to act synergistically, and together had a lower threshold than either compound alone [42]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimball [41] pointed out that dilution and degradation during ripening causes a reduction in limonin levels. Dea et al [42] reported that limonin and nomilin were shown to act synergistically, and together had a lower threshold than either compound alone [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Even though bitterness is considered to negatively impact OJ [42], a certain degree of bitterness is expected, and when combined with other desirable attributes, such as caffeine in coffee and alcohol in wine, bitterness can be an acquired taste in juice [43,44]. …”
Section: Resultsmentioning
confidence: 99%
“…However, for a compound to have taste impact, it has to be present in amounts that exceed its detection threshold. For each cultivar, at 0–4 h, the concentrations of limonin were below its detection threshold (4.7 mg L −1 ) in juice as reported by Dea et al Limonin concentrations in ‘Navel’ and USDA 1‐105‐106 juices held for 24 h or more were often above the detection threshold, suggesting that there was enough to account for a difference in the perception of bitterness. In contrast to ‘Navel’ and USDA 1‐105‐106, limonin concentrations in ‘Ambersweet’ were lower than the detection threshold, except for freezing at H1.…”
Section: Resultsmentioning
confidence: 57%
“…Panelists in general tend to have more difficulty evaluating bitterness than sweetness or sourness, so more variability is to be expected when rating bitterness . This explains the higher panelist variability observed for bitterness ratings compared with sweetness and sourness ratings (data not shown).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation